KEANEKARAGAMAN LIKEN PULAU TUNDA BANTEN SEBAGAI KONTEN PEMBELAJARAN KEANEKARAGAMAN HAYATI BERBASIS POTENSI LOKAL - Pipit Marianingsih; Evi Amelia; Niska Nurhayati (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2017)
AbstractLocal potency-based learning content is important as an effort to reveal local potentials in a region, further to gain  students’s knowledge and environmental awareness in managing and using the natural resourches for society welfare. Banten Province is known has high biodiversity, including lichen. Lichen is a mutualism symbiotic association between a fungus and algae, which has important role in environment, known as indicators of pollution, and also contribute in biological weathering. This study aim to determine the diversity of Lichen at Tunda Island, one of the 17 islands in Serang, Banten Province, to be applied as biodiversity content on local potency-based teaching learning at school. The research method used were exploration to know the diversity of lichen, and research and development (R & D) method to analyze learning content.  Based on the exploration results found 21 species of Lichen on Tunda Island, consists of 16 species of crustose and 5 species of foliose. The lichen diversity index (H ') at three research stations, ranged 0.629 to 1.067, including low to moderate. These contents were developed for genetic-level biodiversity and species-level biodiversity learning concept.